Ambiguity Of The Verdict On The Position Of Multiple Certificates On The Object Of Land Disputes - Veronika T; Fitri Rafianti (LITERACY : International Scientific Journals of Social, Education, Humanities, 2023)
In Government Regulation Number 24 of 1997 concerning Land Registration Article 3 the purpose of land registration is to provide legal certainty and protection to holders of rights to a plot of land, apartment units and other rights registered in order to easily prove themselves as the holder of the rights concerned, to provide information to interested parties including the Government in order to easily obtain the necessary data in Conduct legal actions regarding land parcels and units of flats that have been registered and for the orderly implementation of land administration. The problem that often arises in the community is the existence of a Certificate of Land Rights issued on the same land object. In this case, the issuance of the Certificate of Land is the authority of the Ministry of Agrarian and Spatial Planning / National Land Agency of the Republic of Indonesia (hereinafter referred to as the Ministry of ATR / BPN RI). The issuance of more than 1Certificate of Land Rights on the same land object causes problems, so there is a need for the role of the judiciary to solve the problem. The object of the lawsuit is SHM Number. 531 Ds. Buluh Pancur covering an area of approximately 44,365.m2 in 1983. The result of the decision states that the Inadmissible Lawsuit (niet ontvankelijke verklaard / NO) is a formal defective decision which means that the lawsuit is not followed up by the judge to be examined and tried so that there is no object of the lawsuit in the decision to be executed. While in the 2nd Judgment in the lawsuit to PT. TUN (High Administrative Court number 166/B/2020/PT..TUN-MDN). In the lawsuit it was inadmissible, so the plaintiff filed an appeal legal remedy which resulted in a Level 1 Judgment being canceled by the panel of judges and declared void and required the defendant, namely the National Land Agency (BPN). In the Supreme Court decision No. 610 k / tun 2020, the plaintiffs and intervening defendants filed cassation on the result, namely canceling the appeal decision, adjudicating itself, accepting the exception of the subject matter, stating that the lawsuit was not accepted so that overlapping overlaps could be resolved along with cancellation.